2021
DOI: 10.1016/j.redox.2020.101840
|View full text |Cite
|
Sign up to set email alerts
|

A redox-mediated conformational change in NQO1 controls binding to microtubules and α-tubulin acetylation

Abstract: The localization of NQO1 near acetylated microtubules has led to the hypothesis that NQO1 may work in concert with the NAD + -dependent deacetylase SIRT2 to regulate acetyl α-tubulin (K 40 ) levels on microtubules. NQO1 catalyzes the oxidation of NADH to NAD + and may supplement levels of NAD + near microtubules to aid SIRT2 deacetylase activity. While HDAC6 has been shown to regulate the majority of microtubule acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…These microtubule structures contain high levels of acetylated α-tubulin (K40) and NQO1 was shown to co-localize with these acetylated structures in double-immunostaining studies [ 177 ]. Binding of NQO1 dimer to microtubules likely occurs via its positively charged C-terminal tails which are exposed when the enzyme is in the oxidized state [ 177 , 186 ]. A number of NAD + -dependent enzymes including SIRT2 and PARP have also been observed to co-localize with these acetylated microtubule structures suggesting that NQO1 may be providing NAD + for these enzymes [ [187] , [188] , [189] ].…”
Section: Other Potential Roles Of Nqo1 During Oxidative Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…These microtubule structures contain high levels of acetylated α-tubulin (K40) and NQO1 was shown to co-localize with these acetylated structures in double-immunostaining studies [ 177 ]. Binding of NQO1 dimer to microtubules likely occurs via its positively charged C-terminal tails which are exposed when the enzyme is in the oxidized state [ 177 , 186 ]. A number of NAD + -dependent enzymes including SIRT2 and PARP have also been observed to co-localize with these acetylated microtubule structures suggesting that NQO1 may be providing NAD + for these enzymes [ [187] , [188] , [189] ].…”
Section: Other Potential Roles Of Nqo1 During Oxidative Stressmentioning
confidence: 99%
“…The distinct reduced and oxidized conformations of NQO1 have not been structurally characterized but non-denaturing gels clearly show different migratory properties for the reduced and oxidized conformations of the enzyme [ 177 ]. In subsequent studies [ 186 ], it was demonstrated that NQO1 can exist in at least three different conformational forms, a reduced conformation, an oxidized conformation and an inactivated conformation which have different reactivities with antibodies and therefore different implications for reacting with downstream proteins.
Fig.
…”
Section: Other Potential Roles Of Nqo1 During Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations